The Position of the Visum Et Repertum in the Investigation Process of the Crime of Assault by the Rokan Hilir Criminal Investigation Unit - Aldo Fiqri Maulana; Risdalina Risdalina; Kusno Kusno (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
In law enforcement against criminal acts of assault, evidence plays a central role. One piece of evidence that is often key is the Visum et Repertum (VeR) or medical examination report. This article discusses the strategic position of VeR in the investigation process carried out by the Criminal Investigation Unit (Reskrim) of the Rokan Hilir Police, starting from its legal function as evidence to its role as a guide to uncovering the motives and perpetrators of crimes of assault. Legally, VeR has dual power as valid evidence according to Article 184 paragraph (1) of the Criminal Procedure Code (KUHAP), namely as an expert statement from a doctor and as a letter made by a public official. This duality gives it significant legal weight. For investigators from the Rokan Hilir Criminal Investigation Unit, VeR is not just a list of injuries; it is an objective and scientific primary piece of evidence. Its functions include: (1) serving as a basis for qualifying the applicable articles, distinguishing between ordinary, serious, or fatal assault; (2) serving as a verification tool to test the consistency of the statements of witnesses, victims, and suspects; (3) provide clues (indications) regarding the modus operandi, tools used, and chronology of events, which are vital in the reconstruction of events.